Analysis of MCP-1 Levels and TNF-alfa /Il-10 Ratio in First Degree Relatives (FDR) Type 2 Diabetes Mellitus Subjects with High Fat Diet Treatment - Dante Saksono Harbuwono; Heri Wibowo; Risty Yasmin Bonita (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Type 2 diabetes mellitus is a chronic metabolic disease, which involves a variety of pathogenic processes. Overall these processes result in loss of mass and/or function of pancreatic-cells which is manifested as hyperglycemia. The influence of familial factors appears to be involved in the initiation and development of T2DM through both genetic and non-genetic factors. In the same family environment as patients with diabetes, first-degree relatives of patients with diabetes show a 30-70% increased risk of developing diabetes. Insulin resistance and cell dysfunction have been identified in individuals with a family history of diabetes, even before the onset of T2DM symptoms. Monocyte chemoattractant protein-1 (MCP-1) is a CC-chemokine with an attractant effect on monocytes, memory T cells and basophils. Expression of adipose tissue MCP-1 and circulating levels were  positively correlated with adiposity. Larger adipocytes are associated with insulin resistance. This study aims to determine the changes in MCP-1 expression on monocytes before and after treatment with a high-fat diet for five days. The results showed that there was a change in inflammatory activity which was indicated by a high ratio of TNF-alfa/IL – 10 in the FDR group so that it could increase MCP-1 activity. However, there was no relationship between serum MCP-1 levels and the percentage of CD14+CD16+ monocytes in both groups.